2004
DOI: 10.1103/physrevb.70.035205
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational fluorescence spectroscopy of single conjugated polymer molecules

Abstract: Fluorescence spectroscopy of conjugated polymers at the single molecule level provides unique insight into the nature of the emitting state of these organic semiconductors. We are able to verify the picture that molecular excitations form the primary photoexcitations in conjugated polymers by identifying individual chromophore units on rigid rod-like chains of a ladder-type polymer. The observation of a well-defined substructure in the vibronic progression as well as the presence of sum-frequency vibrational m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 71 publications
5
56
0
Order By: Relevance
“…1D). Strong variations in the PL intensity of the vibronic progression between single chromophores have been reported previously, even in nominally rigid materials such as LPPP (51). Such variations arise due to the slight distribution in ground-state molecular conformations, leading to differing structural relaxation energies and the resulting changes in the Franck-Condon progression, which become visible precisely because electronic and vibronic transitions are so narrow at low temperature.…”
Section: Resultsmentioning
confidence: 89%
“…1D). Strong variations in the PL intensity of the vibronic progression between single chromophores have been reported previously, even in nominally rigid materials such as LPPP (51). Such variations arise due to the slight distribution in ground-state molecular conformations, leading to differing structural relaxation energies and the resulting changes in the Franck-Condon progression, which become visible precisely because electronic and vibronic transitions are so narrow at low temperature.…”
Section: Resultsmentioning
confidence: 89%
“…[4g] This effect, which is in part related to structural relaxation (although this is very weak indeed in the ladder-type polymers [19] ), has also been investigated theoretically, [24,25] as a precise knowledge of the size of the emitting and absorbing unit is imperative for understanding and modeling intramolecular energy transfer. [25] The conclusion of extended conjugations naturally raises the question of the origin of static disorder, which gives rise to a distribution in chromophore energies and the associated inhomogeneous broadening witnessed in Figure 2 d. The common notion is that topological defects lead to a confinement of the excitation and thus to a modification in transition energy.…”
Section: Methodsmentioning
confidence: 99%
“…[12][13][14][15][16][17] We recently showed that SMS can provide unique information on the presence of chromophores in CPs and may be used to investigate intramolecular interchromophoric couplings. [18][19][20][21] Single chromophores exhibit universal photophysical properties independent of the details of the materials chemistry, thus enabling the derivation of universal structure-property relationships. [21] Herein we address the fundamental issue of how the number of chromophores varies with molecular size (i.e.…”
mentioning
confidence: 99%
“…1b to emission from a single chromophore unit. The PL is linearly polarized in emission and absorption (22,24,25). We recently reported multiple line emission from single MeLPPP molecules and suggested that this corresponds to emission from a number of chromophore units on the chain (22).…”
Section: ϫ8mentioning
confidence: 98%